Kompetensi Yang Tepat, Lingkungan Yang Kondusif: Resep Kinerja Optimal di Industri Penerbangan - Nuryulianti; Soekotjo, Sundari (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the effect of employee engagement, competence, and work environment on employee performance with job satisfaction as a mediating variable at PT. Aerofood Indonesia. A quantitative approach with a survey method was employed, involving 235 respondents selected using a non-probability sampling technique with the purposive sampling method. Data were collected through a Likert-scale-based questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the direct effect test indicate that employee engagement and competence do not significantly affect job satisfaction, while the work environment has a significant effect on job satisfaction. Employee engagement, competence, work environment, and job satisfaction significantly influence employee performance. Based on the path analysis, job satisfaction cannot mediate the effect of employee engagement, competence, and work environment on employee performance. The model analysis shows that the research model falls into the moderate to strong category with medium predictive relevance.